Adaptive Governance and the Complexity of Smart Tourism Policy in West Nusa Tenggara - Rifaid Rifaid; Ayatullah Hadi; Amil Amil; Laila Nur Amalia; Fransiska Yasinta Riang (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2026)
The purpose of this study is to analyze and optimize the implementation of smart tourism in supporting sustainable tourism development in West Nusa Tenggara through an adaptive governance approach. The research method is a qualitative comparative study. Data collection was carried out through interviews, documentation, observation, and Focus Group Discussions (FGDs). Data analysis was conducted using NVivo 12 Plus, with coding, data visualization, and source triangulation to ensure the validity and reliability of the research findings. The research findings indicate that the development of smart tourism in West Nusa Tenggara has great potential to increase regional competitiveness and economic growth. However, the effectiveness of its implementation depends heavily on integrating digital infrastructure, human resource capacity, and adaptive governance. Despite having superior destinations and government policy support, there are still gaps in the distribution of digital infrastructure and system integration. The use of data in tourism management is still partial and not optimally integrated. Furthermore, fluctuations in tourist visits underscore the need for flexible, data-driven policies. Therefore, strengthening digital architecture, increasing human resource capacity, and fostering cross-sector collaboration are key to optimizing smart tourism. In conclusion, the success of smart tourism depends on integrating technology, adaptive policies, and a systemic, sustainable collaboration.